Information Systems for Indian Languages International Conference, ICISIL 2011, Patiala, India, March 9-11, 2011. Proceedings - Singh, Chandan; Singh Lehal, Gurpreet; Sengupta, Jyotsna; Sharma, Dharam Veer.; Goyal, Vishal; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
This book constitutes the refereed proceedings of the International Conference on Information Systems for Indian Languages, ICISIL 2011, held in Patiala, India, in March 2011. The 63 revised papers presented were carefully reviewed and selected from 126 paper submissions (full papers as well as poster papers) and 25 demo submissions. The papers address all current aspects on localization, e-governance, Web content accessibility, search engine and information retrieval systems, online and offline OCR, handwriting recognition, machine translation and transliteration, and text-to-speech and speech recognition - all with a particular focus on Indic scripts and languages.
Keywords: Computer science; Algorithms; Mathematical logic; Data mining; Artificial intelligence; Text processing (Computer science).; Computational linguistics; Computer Science; Artificial Intelligence (incl. Robotics).; Mathematical Logic and Formal Languages; Language Translation and Linguistics; Data Mining and Knowledge Discovery; Algorithm Analysis and Problem Complexity; Document Preparation and Text Processing; Electronic books